新加坡的华文同志剧场（1992—2011 年）= Chinese gay theatre in Singapore (1992–2011) - 黄爱莉 Ng, Shirleywijaya Ai Li (2012)
“同性恋”作为一个异性恋霸权主义社会中的敏感课题，存在于新加坡的法律条文和社会观念除了限制着同志的生活外，同时也影响着大众对他们所持有的态度。由于同志行为和规范的异性恋爱情模式并不相符，因此同志往往是社会中被边缘化的群体。当新加坡的艺术文化随着国家的发展与审查制度的放松而得以蓬勃时，如同志般的边缘性／别议题得以通过剧场，一个适合对附有争议性的课题进行探索的小众媒体，来表达自我与宣誓自己的权利。 本文以新加坡华文同志剧场发表第一部同志剧作的1992年为上限，2011年为下限，试图通过了解新加坡同志剧场的社会历史语境、新加坡华文同志剧场的起源和发展过程中华文同志剧场性质上的转变，以及以女权主义者巴特勒的表演性理论为基础来分析1992－2011年间的四部附有代表性的剧作，来探讨新加坡华文同志剧场的意义与作用。In a heterosexist country like Singapore, where heterosexual relationships are promoted as morally correct and part of the social norm, homosexuality remains a sensitive social issue and at times, a taboo. The presence of the law and traditioanl Asian values restrict the homosexual lifestyle, and therefore our citizens’ attitudes towards homosexuals are also very much influenced by what is regarded as unacceptable by the country. As homosexuality poses as an opposing relationship model in contrast to a heterosexual relationship, homosexuals in Singapore are often marginalised. The local arts scene gradually flourished alongside the country’s development, and censorship restrictions were reportedly relaxed. In the late 80s, playwrights began to experiment gay themes on the Singaporean stage. Thus, the theatre became a place for marginalised communities such as homosexuals, to express themselves and their rights. The Singapore Gay Theatre also began to push boundaries by presenting plays that touched on sensitive and taboo topics. With a boundary of discourse set between 1992 -- the year in which the first Chinese gay play was released locally -- and 2011, this thesis aims to discuss the meaning and purpose of the Chinese Gay Theatre in Singapore, through understanding the Singapore Gay Theatre’s social historical context, the development of the Singapore Chinese Gay Theatre and the changes in its nature over time, as well as providing an analysis on four plays performed to public over the period of 1992 – 2011, on the basis of Judith Butler’s theory of performativity.